Chondrogenic differentiation of human bone marrow‐derived mesenchymal stromal cells in a three‐dimensional environment. Issue 4 (25th September 2019) - Salonius, Eve; Kontturi, Leena; Laitinen, Anita; Haaparanta, Anne‐Marie; Korhonen, Matti; Nystedt, Johanna; Kiviranta, Ilkka; Muhonen, Virpi
Abstract: Cell therapy combined with biomaterial scaffolds is used to treat cartilage defects. We hypothesized that chondrogenic differentiation bone marrow‐derived mesenchymal stem cells (BM‐MSCs) in three‐dimensional biomaterial scaffolds would initiate cartilaginous matrix deposition and prepare the construct for cartilage regeneration in situ. The chondrogenic capability of human BM‐MSCs was first verified in a pellet culture. The BM‐MSCs were then either seeded onto a composite scaffold rhCo‐PLA combining polylactide and collagen type II (C2) or type III (C3), or commercial collagen type I/III membrane (CG). The BM‐MSCs were either cultured in a proliferation medium or chondrogenic culture medium. Adult human chondrocytes (ACs) served as controls. After 3, 14, and 28 days, the constructs were analyzed with quantitative polymerase chain reaction and confocal microscopy and sulfated glycosaminoglycans (GAGs) were measured. The differentiated BM‐MSCs entered a hypertrophic state by Day 14 of culture. The ACs showed dedifferentiation with no expression of chondrogenic genes and low amount of GAG. The CG membrane induced the highest expression levels of hypertrophic genes. The two different collagen types in composite scaffolds yielded similar results. Regardless of the biomaterial scaffold, culturing BM‐MSCs in chondrogenic differentiation medium resulted in chondrocyte hypertrophy. Thus, caution for cell fate is required when designing cell‐biomaterial constructs for cartilage regeneration. Abstract : The purpose of the study was to investigate, whether chondrogenic predifferentiation of bone marrow‐derived mesenchymal stem cells (BM‐MSCs) in novel three‐dimensional biomaterial scaffolds would initiate cartilaginous matrix deposition and whether the type of collagen used in the scaffolds would affect the results. The two different collagen types in composite scaffolds yielded similar results. Regardless of the biomaterial scaffold, culturing BM‐MSCs in chondrogenic differentiation medium resulted in chondrocyte hypertrophy.